Persepsi Nelayan Terhadap Dampak Program Pemberdayaan Masyarakat (Studi Kasus Kampung Madong Kota Tanjungpinang): Socio-Economic Characteristics of Fishermen Recipients of the Community Empowerment Program in Madong Village, Tanjugpinang City - Nasihin, Daratun; Khodijah, Khodijah; Reni, Angga (Department of Socio-economic Fisheries, Marine Science and Fisheries Faculty, Universitas Maritim Raja Ali Haji, 2024)
ABSTRACT. The purpose of this study was to identify the type of program, socio-economic characteristics of program recipients, perceptions of fishermen, and constraints on program implementation. This research was carried out in early July to late August 2021 in Madong Village, Bugis Village, Tanjungpinang City District. This research method uses a qualitative descriptive approach. The sample determination is 25% of a total of 143 fishermen, so that the total sample in this study is 35 people and 3 key informants. The data analysis used is descriptive analysis. There are 7 types of empowerment programs in Madong village (PKH, BPNT, BSPS, KUSUKA, facilities assistance from KKP, infrastructure assistance from DP3, KEM) The socio-economic characteristics of program recipients consist of social aspects, namely housing conditions, education, family size, type of work and social groups meanwhile from the economic aspect consist of capital, income, work system and production system